Novel dyed ethylene-norbornene composites with enhanced aging resistance. (January 2016) - Marzec, Anna; Chrzescijanska, Ewa; Boruszczak, Zygmunt; Zaborski, Marian; Laskowska, Anna; Boiteux, Gisèle; Gain, Olivier
Abstract: The current research investigated the effects of anthraquinone solvent dyes and commercial stabilizers on the aging resistance properties of ethylene-norbornene (EN) composites subjected the aging in the full solar-spectrum for various time periods. During irradiation, the mechanical properties were measured by low and high degrees of deformation using dynamic mechanical analysis (DMA) and tensile tests until break, respectively. Changes in the color and surface defects in the investigated composites were evaluated using spectrophotometry and scanning electron microscopy (SEM). An accelerated aging test revealed that the application of solvent dyes with anthraquinone chromophores significantly prolonged the lifetimes of the EN composites during aging. The best improvement in durability was found in the EN samples that contained dyes, such as Solvent Blue 97, Solvent Blue 104, Solvent Blue and Solvent Green 28. Moreover, the ability of solvent dyes to protect EN composites against harmful effects of solar radiation was found to be much greater comparing to those of the investigated, commonly used stabilizers. Graphical abstract: